In This Issue—Confronting Birth Inequity (J Perinat Educ, 2019)
In this column, the editor of The Journal of Perinatal Education discusses the growing issue of confronting birthing inequity and factors impacting maternal morbidity and mortality. The editor also describes the contents of this issue, which offer a broad range of resources, research, and inspiration for childbirth educators in their efforts to promote, support, and protect natural, safe, and healthy birth.